Survival of Staphylococcus aureus, Listeria monocytogenes, and Salmonella spp. in traditional Tomas cheese during the ripening at different temperatures - Mutlu, Muhsin; Incili, Gokhan Kursad; Calicioglu, Mehmet (Elsevier, 2026)
This study aimed to investigate the viability of Listeria monocytogenes, Staphylococcus aureus, and Salmonella spp. in Tomas cheese produced by traditional methods and ripened at 4 C-degrees and 10 C-degrees. Fresh Tomas cheese samples were inoculated with a cocktail of Staphylococcus aureus, Listeria monocytogenes, and Salmonella spp. (approximately 4.0-5.0 log10 CFU/g) and then pressed into plastic jars and stored at 4 C-degrees and 10 C-degrees. Chemical and microbiological analyses of the cheese were performed on days 0, 7, 15, 30, 45, 60, 90, and 120. At the end of the ripening period, the mean reductions in pathogen counts in the groups stored at 4 C-degrees and 10 C-degrees were 4.54 and 3.15 log10 CFU/g for Salmonella spp. (p < 0.001), 1.59 and 1.75 log10 CFU/g for Staphylococcus aureus, and 2.92 and 3.06 log10 CFU/g for Listeria monocytogenes, respectively. The total viable counts (TVC), psychrotrophic bacteria, Lactobacillus spp., Lactococcus spp., Enterococcus spp., proteolytic bacteria, lipolytic bacteria, mold and yeast counts remained within the 4-7log10 CFU/g range with only slight fluctuations during the ripening period, and no significant differences were detected between the groups at the two storage temperatures. As a result, although Staphylococcus aureus, Salmonella spp., and Listeria monocytogenes counts decreased at two both ripening temperatures (4 C-degrees and 10 C-degrees) by the end of the ripening period, the data suggest that these pathogenic microorganisms may still pose a potential food safety risk to public health in Tomas cheese.
Keywords: Tomas cheese; food safety; traditional; chemical; microbiological